Pengaruh Metode Sintesis Silika Mesopori SBA-15 terhadap Analisis Differential Scanning Calorimetry dan Pengukuran Low Angles X-Ray Diffraction - Ridhawati, Ridhawati; Wahab, Abdul Wahid; La Nafie, Nursiah; Raya, Indah (INTEK: Jurnal Penelitian, 2018)
Mesoporous silica SBA-15 is an interesting material having highly ordered nanopores and large surface area, which is synthesized by sol gel and hydrothermal methods. In this study, mesoporous silica SBA-15 was synthesised with two different methods and the characteris was using X-Ray Diffraction (XRD) and Differential Scanning Calorimetry (DSC). SBA-15 was prepared TEOS as precursor and Pluronic 123 as surfactant. Thermoporous mesoporous DSC thermogram results of the SBA-15A mesoporous silica is (Tg 79oC and Tc 158oC). This is relatively lower than SBA-15B (Tg 86oC and Tc 158oC). The measurement of low angle X-Ray Diffraction SBA-15A has a crystal size 9.46 nm and SBA-15B has a crystal size 9.96 nm. The synthesis of SBA-15 using the hydrothermal method needs to be studied further to obtain thermal characteristics and a more stable crystal structure